Communication about Alzheimer's disease and research among American Indians and Alaska Natives - Amanda D. Boyd; Ashley F. Railey; Alex W. Kirkpatrick; Ying‐Chia Hsu; Clemma Muller; Dedra Buchwald (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction American Indian and Alaska Native (AI/AN) people infrequently participate in Alzheimer's disease (AD) research, despite the rapidly increasing population of AI/AN people aged 65 and older. Methods We surveyed 320 adults who identified as AI/AN at two Native‐focused events and used ordinary least squares regression and logistic regression models to test associations between demographic factors and perceived risk of AD, knowledge about AD, and willingness to participate in research, along with preferred source of AD information. Results Willingness to participate in research was highest among those living in a city versus reservation and associated with perceived personal risk for AD. Health professionals and the internet were preferred sources of information about AD. Discussion These hypothesis‐generating results provide insight into perceptions of AD and willingness to participate in research. Conclusions could inform development of AD recruitment strategies for AI/ANs and influence participation in AD research.